Current status of and progress in the treatment of malignant pleural effusion of lung cancer - Zhao, Yuhua; Yu, Limeng; Wang, Lili; Wu, Yingxi; Chen, Haiyang; Wang, Qiming; Wu, Yufeng (Frontiers in Oncology, 2023)
Malignant pleural effusion is a common complication in the late stage of malignant tumors. The appearance of malignant pleural effusion indicates that the primary tumor has spread to the pleura or progressed to an advanced stage. The survival time of the patients will be significantly shortened, with a median survival of only a few months. There are a variety of traditional treatments, and their advantages and disadvantages are relatively clear. There are still many problems that cannot be solved by traditional methods in clinical work. At present, with the development of medical technology, there are a variety of treatment methods, and many innovative, significant and valuable treatment methods have emerged, which also bring hope for the treatment of refractory and recurrent malignant pleural effusion patients. However, there is still a long way to go to completely control and cure malignant pleural effusion, and the organic combination of clinical work and scientific research results is needed to bring dawn to refractory malignant pleural effusion patients.